2001
DOI: 10.1136/gut.48.3.360
|View full text |Cite
|
Sign up to set email alerts
|

Tumour infiltrating lymphocytes and apoptosis are independent features in colorectal cancer stratified according to microsatellite instability status

Abstract: + and M30 + random apoptosis counts (p<0.001). However, TILs and apoptosis showed little colocalisation. Conclusions-While TILs might be expected to explain the increased apoptotic rate and improved prognosis of MSI-H cancers, it is likely that TILs and apoptosis are independent characteristics of MSI-H cancers. (Gut 2001;48:360-366)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
139
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(159 citation statements)
references
References 19 publications
12
139
2
2
Order By: Relevance
“…Stromal MSI presented in this study might be due to the methylation of mismatch repair enzymes in stromal cells, although the identification of the enzyme remains unclear. Previously, it was shown that high-level MSI (MSI-H) tumours are more likely to be right sided than their low-level MSI (MSI-L) or MSI stable counterparts (Michael-Robinson et al, 2001;Ward et al, 2001). In the present study, while MSI frequencies in both the epithelium and stroma were high in right-side (43, 50%) as compared to left-side lesions (29, 36%), the difference did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Stromal MSI presented in this study might be due to the methylation of mismatch repair enzymes in stromal cells, although the identification of the enzyme remains unclear. Previously, it was shown that high-level MSI (MSI-H) tumours are more likely to be right sided than their low-level MSI (MSI-L) or MSI stable counterparts (Michael-Robinson et al, 2001;Ward et al, 2001). In the present study, while MSI frequencies in both the epithelium and stroma were high in right-side (43, 50%) as compared to left-side lesions (29, 36%), the difference did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 90%
“…However, the contribution of stromal cells to the generation and progression of epithelial neoplasia has not been thoroughly investigated. Although genetic alterations are frequently observed in many benign and malignant epithelial tumours in the form of microsatellite instability (MSI) (Michael-Robinson et al, 2001;Ward et al, 2001), the possibility of genetic abnormalities in the background microenvironment of these tumours has generally not been addressed properly. However, recent findings indicate that loss of heterozygosity (LOH) may be frequent in mammary stromal tissue in breast cancer patients (Moinfar et al, 2000).…”
mentioning
confidence: 99%
“…Guidoboni et al [72] showed a significantly higher prevalence of activated CD8 + IEL in MSI+ versus MSI-CRC, suggesting that the occurrence of a local cytotoxic immune response may be the major determinant of the good clinical course of these MSI+ CRC patients. Dolcetti et al [71] and Michael-Robinson et al [73] demonstrated that the increased frequency of TILs associated with MSI-H cancers are only weakly or moderately correlated with tumor apoptosis. However, while TILs might be expected to explain the increased apoptotic rate and improved prognosis of MSI-H cancers, it is likely that MSI-H cancers are intrinsically more prone to apoptosis, independently of T cell attack [73].…”
Section: Role In Prognosismentioning
confidence: 99%
“…Dolcetti et al [71] and Michael-Robinson et al [73] demonstrated that the increased frequency of TILs associated with MSI-H cancers are only weakly or moderately correlated with tumor apoptosis. However, while TILs might be expected to explain the increased apoptotic rate and improved prognosis of MSI-H cancers, it is likely that MSI-H cancers are intrinsically more prone to apoptosis, independently of T cell attack [73]. In addition, Buckowitz et al [74] and Chiba et al [52] suggested a protective role of functionally active lymphocytes directed against MSI-H CRCs, which may prevent tumor cell dissemination and metastasis formation in distant organs.…”
Section: Role In Prognosismentioning
confidence: 99%
“…The number of intraepithelial CD3ϩ cells in the 5 most infiltrated fields were counted and the average number of the CD3ϩ cells/1,000 neoplastic cells was scored as low (Ͻ50), moderate (51-70) or high (Ͼ71). 20 …”
Section: Immunohistochemistrymentioning
confidence: 99%